Relationship between workload and job satisfaction of nurses in the hospitalization room: A literature review - Yanwarin, Jean Ayu C (Indonesian Journal of Health Services, 2024)
Background: High workload among nurses in hospitalization rooms frequently influences job satisfaction and healthcare service quality. These conditions often arise from high patient demands, staffing shortages, and administrative responsibilities. Objective: This study aims to analyze the relationship between workload and job satisfaction among nurses working in hospitalization rooms through a literature review. Methods: This study employed a literature review method by collecting and analyzing scientific articles published in academic databases such as Google Scholar between 2019 and 2023. The study selection process followed the PRISMA guideline from the EQUATOR Network. The selected articles examined workload conditions, job satisfaction, and organizational factors affecting nurses in hospital settings. Results: The review found that most nurses experience high workload due to high patient volume, shift work systems, and complex administrative tasks. High workload conditions were associated with increased fatigue, job stress, and decreased job satisfaction among nurses. Organizational support, work environment, and work–life balance were also identified as important factors influencing nurses’ job satisfaction. Conclusion: Workload shows a negative relationship with job satisfaction among nurses in hospitalization rooms. Effective workload management strategies are necessary to improve nurses’ well-being and healthcare service quality.